TEACHING READING BY VISUALIZATION AS A STRATEGY - Yeni Erlita (BAHAS, 2021)
Abstract  This study aims to determine if visualizing when teaching reading learners is beneficial in reading comprehension for students. One of the ways for teaching reading is visualization. It is the ability of a student to visualize what he or she is reading. Students learn to develop mental pictures to aid comprehension and recall in this method. And students can increase their comprehension of written content by creating mental representations. It increases students' focus, attention to detail, and independent reading skills by assisting them in transforming words into higher-level concepts. And teacher can make students work in pairs and allow them to work through the texts together from different subject areas. It can be inferred that teaching reading to young learners through visualization strategy is effective in reading comprehension for students.                            Keywords: teaching, reading, students, visualization, comprehension.